2008
DOI: 10.1136/jech.2007.063149
|View full text |Cite
|
Sign up to set email alerts
|

Cultural identity, clothing and common mental disorder: a prospective school-based study of white British and Bangladeshi adolescents

Abstract: Objective: Cultural integration is the healthiest outcome for young people living in multicultural societies. This paper investigates the influence of different cultural identities on the risk of common mental disorders among Bangladeshi and white British pupils. Design: The cultural identity of 11-14-year-old school pupils was assessed by their preferences for friends and clothes of their own or other cultural groups; using this information pupils were classified into traditional, integrated, assimilated or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 44 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…To date there is a dearth of data concerning how ethic minority groups use religious coping in the context of distress. Bhui, King, Dein, and O’Connor (2008) undertook a large public health study of six ethnic groups in the UK in the EMPIRIC study. A qualitative component comprised 116 people.…”
Section: Religion and Mental Healthmentioning
confidence: 99%
“…To date there is a dearth of data concerning how ethic minority groups use religious coping in the context of distress. Bhui, King, Dein, and O’Connor (2008) undertook a large public health study of six ethnic groups in the UK in the EMPIRIC study. A qualitative component comprised 116 people.…”
Section: Religion and Mental Healthmentioning
confidence: 99%
“…28 People may not define themselves as being in the same ethnic group over time, 29 so self ascribed ethnicity should be viewed as a proxy for how people view their membership of an ethnic grouping 28 30 and does not necessarily tap into notions of "cultural identity." 28 Recent research has, for example, suggested that cultural practices associated with cultural identity could be associated with mental health benefits 31 and could "govern forms of social support, gender disadvantage and access to employment" 28 ; therefore future research could examine how far cultural identity may mediate ethnic density effects, although attempting to assess "identity" may present additional challenges.…”
Section: Implications and Comparison With Other Studiesmentioning
confidence: 99%
“…Cultural integration was associated with a lower prevalence of mental health problems in cross-sectional analyses, but these did not exclude reverse causality as a possible explanation 16 , 18 . Therefore, longitudinal studies of cultural integration are necessary as are comparative studies using similar methods in different cultural groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, this process places strain on social relationships (within and across ethnic groups) and can affect mental health 15 . International research shows that acculturation can lead to a change in choice of friendships, clothing, consumption behaviours, preferred language, choice of reading materials and leisure activities, religious practices and parenting style 16 , 17 . The research methods used to measure acculturation and the cultural groups under investigation often differ across studies, making it difficult to draw any comparative conclusions across ethnic groups, and within the same country, let alone across countries 17 .…”
Section: Introductionmentioning
confidence: 99%